Study on blast-induced ground vibration velocity limits for slope rock masses - Sun, Jinshan; Jia, Yongsheng; Zhang, Zhen; Yao, Yingkang (Frontiers in Earth Science, 2023)
Seismic waves induced by blasting can cause damage to slope rock masses and thus lower the stability of the slope. The vibration standards of many countries do not specify the allowable blasting vibration velocity for slope rock masses. “Blasting Safety Regulations” (GB 6722-2014) in China recommends the allowable blasting vibration velocity of slope rock masses. However, the strength of rock mass and geometric characteristics of slope are not considered in the criterion. Therefore, based on the wave equation of Rayleigh wave, the mathematical relationship between the additional dynamic stress of the rock mass near the slope surface and the peak particle velocity (PPV) on the ground is analyzed. Under the control conditions that no tensile and shear damage occur in the slope, a calculation method of allowable blasting vibration based on a simple slope model is proposed, in which the strength of rock mass and the geometric characteristics of the slope are considered. The theoretical basis of the proposed method is verified by numerical experiments. Based on the field test results of the slope of Xiaowan Hydropower Station, the proposed method was verified further. The damage control target of the rock mass determined by the proposed method was in good agreement with the actual damage detection result.